Penerapan Media Storyjumper dan Storytelling Sebagai Sarana Literasi Digital Sekolah MI Raden Rahmat - Hariyani, Indaria Tri; Soemarmi, Soemarmi; Nurhidayah, Sri; Prameswari, Noviardani Kartika; Fitri, Norma Diana (PT. Riset Press International, 2023)
This community service aims for both teachers and education staff to be able to implement digital literacy-based activities that use storyjumper and storytelling media for students at the MI Raden Rahmat school. The research method used is a combination (Mixed Research) by adopting the Kemmis and Mc Taggart model. There are 5 stages in implementing community service, namely: problem identification, action planning, action implementation, observation and reflection. Observations are carried out in two ways, namely observation and tests. Based on the results obtained, data on educators' knowledge in using storyjumper and storytelling media with an average score of 76.30. The score obtained was described as very good. In conclusion, overall the researchers have carried out the activities well, but educators need to use storyjumper and storytelling media themselves to apply to students when learning at the MI Raden Rahmat school